Perovskite / crystalline silicon laminated solar cell and preparation method thereof
By introducing a two-dimensional perovskite active layer and a surface reconstruction layer into a perovskite/crystalline silicon stacked solar cell, the problem of poor residual stress release of perovskite thin films is solved, and the stability and photoelectric conversion efficiency of the battery are improved.
Patent Information
- Application Number
- CN202510107909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
AI Technical Summary
The existing perovskite solar cells are unable to effectively release the residual stress generated by the perovskite film during the preparation process, resulting in poor stability and low photoelectric conversion efficiency.
A perovskite/crystalline silicon stacked solar cell structure is adopted, in which a two-dimensional perovskite active layer is provided on the surface of the three-dimensional perovskite active layer, and a surface reconstruction layer is introduced between the two-dimensional perovskite active layer and the second carrier transport layer. The material of the surface reconstruction layer is a solid organic acid with a pKa of 3 to 6.
By releasing the internal stress of the three-dimensional perovskite active layer, passivating surface defects, reducing non-radiative recombination, and improving the stability and photoelectric conversion efficiency of perovskite/crystalline silicon stacked solar cells.
Smart Images

Figure CN119907395A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite / crystalline silicon stacked solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have the characteristics of high photoelectric conversion efficiency (PCE), low cost, excellent optical properties and simple preparation. Among them, stacked structure cells have been generally regarded as one of the effective technical paths to improve battery performance. The basic principle is to regard the solar spectrum as different parts, and use solar cell materials with bandgap widths matching different spectral bands to make a stacked cell structure to maximize the conversion of light energy into electrical energy. In particular, due to the high light absorption and bandgap adjustability of perovskite materials, the rapid development of perovskite / crystalline silicon stacked solar cells in recent years is obvious to all, and its conversion rate has increased from less than 23% in 2017 to 29.1% in 2020.
[0003] However, the organic components inherent in perovskite materials are prone to irreversible structural phase changes or rapid decomposition into PbI under conditions of high temperature, high humidity and high oxygen partial pressure. 2 , which affects the stability and photoelectric conversion performance of perovskite solar cells. In order to solve this problem, some researchers have proposed to use FAPbI 3 (FA is formamidine) The introduction of metal cesium cations with a smaller radius (Cs + ) or methylamine cation (MA + ) to form a double cation or trication perovskite film with an appropriate tolerance factor, thereby improving the stability of the perovskite material. At the same time, external physical packaging technology (such as packaging tape or encapsulant) can isolate water vapor in the natural environment to a certain extent, improving the stability and life of perovskite solar cells, but perovskite films still have inherent stability problems, which limits the long-term durability of perovskite solar cell devices.
[0004] In addition to the inherent influencing factors such as perovskite materials and structures, the residual stress generated during the high-temperature annealing and cooling stages of the perovskite film preparation process is a key factor affecting its intrinsic stability. This stress mainly comes from two aspects: (1) the difference in thermal expansion coefficient between the perovskite material and the substrate material; (2) the lattice mismatch between the perovskite material and the substrate material. The release of the above two types of residual stress is crucial to improving the stability and performance of perovskite films, but it has not yet been effectively resolved.
[0005] In summary, researching and developing a perovskite / crystalline silicon tandem solar cell with good stress release effect and few interface defects and a preparation method thereof are of great significance to improving the interface energy level matching, photoelectric conversion efficiency and stability of perovskite / crystalline silicon tandem solar cells. Summary of the invention
[0006] The main purpose of the present invention is to provide a perovskite / crystalline silicon stacked solar cell and a preparation method thereof, so as to solve the problems in the prior art of poor stability and low photoelectric conversion efficiency caused by the inability to effectively release the residual stress generated by the high-temperature annealing and cooling stages of the perovskite film during the preparation process.
[0007] In order to achieve the above-mentioned objectives, on the one hand, the present invention provides a perovskite / crystalline silicon tandem solar cell, which comprises a crystalline silicon bottom cell, a first carrier transport layer, a three-dimensional perovskite active layer, a two-dimensional perovskite active layer, a surface reconstruction layer, a second carrier transport layer and a metal electrode layer stacked in sequence, wherein the material of the surface reconstruction layer is a solid organic acid, and the pKa of the solid organic acid is 3 to 6.
[0008] Furthermore, the solid organic acid is selected from one or more of the group consisting of monobasic acid, dibasic acid and polybasic acid; preferably, the pKa of the solid organic acid is 3 to 4; preferably, the solid organic acid is selected from one or more of the group consisting of lactic acid, malic acid, tartaric acid, citric acid, oxalic acid and succinic acid; preferably, the thickness of the surface reconstruction layer is 20 to 40 nm.
[0009] Furthermore, a stress release layer is provided between the first carrier transport layer and the three-dimensional perovskite active layer. The material of the stress release layer is an organic polymer. The glass transition temperature of the organic polymer is 90 to 250°C, preferably 100 to 180°C, and the weight average molecular weight is 100 to 15,000,000, preferably 1,000 to 60,000.
[0010] Furthermore, the organic polymer has a structure represented by general formula (I), (II) or (III):
[0011]
[0012] Among them, R 1 Selected from hydrogen, C 1 ~C 10 A straight chain or branched alkyl group, or a halogen; n 1 Any integer selected from 1 to 60; R 2 and R 3 are each independently selected from hydrogen, C 1 ~C 10 Straight or branched alkyl, C 1~C 10 Straight chain or branched chain alkoxy, or halogen; n 2 Any integer selected from 1 to 30; R 4 and R 5 are each independently selected from hydrogen, C 1 ~C 10 A straight chain or branched chain alkyl, or a halogen; R 4 and R 5 Same or different; n 3 is any integer selected from 1 to 20; preferably, R 1 Selected from hydrogen, C 5 ~C 8 A straight or branched alkyl group, or F, more preferably hydrogen, n 1 is selected from any integer between 40 and 50; preferably, R 2 Selected from C 1 ~C 8 The straight chain alkoxy group, R 3 With R 2 Same, n 2 Any integer selected from 20 to 25; R 4 Selected from C 1 ~C 8 The branched alkyl group, R 5 With R 4 Same, n 3 is selected from any integer between 10 and 15; more preferably, R 2 and R 3 More preferably, R 4 and R 5 Both
[0013] Furthermore, the thickness of the stress release layer is 10-20 nm.
[0014] Further, the organic polymer is selected from one or more of the group consisting of polystyrene, poly[(m-m-phenylene vinylene)-co-(2,5-dioctyloxy-p-phenylene vinylene)] and poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-B:3,4-B']dithiophene-2,6-diyl]].
[0015] Furthermore, the thickness of the three-dimensional perovskite active layer is 300-500 nm, and the band gap is 1.78-2.03 eV; preferably, the material of the three-dimensional perovskite active layer is ABX 3 , wherein A is selected from CH 3 NH 3 + NH=CHNH 3+ and Cs + One or more of the group consisting of; B is selected from Pb 2+ and / or Sn 2+ ; X is selected from Cl - Br - and I - One or more of the groups.
[0016] Furthermore, the thickness of the two-dimensional perovskite active layer is 100-300 nm, and the band gap is 1.4-2.5 eV; preferably, the material of the two-dimensional perovskite active layer is L 2 A m-1 M m X 3m+1 , where L is selected from C 4 H 9 NH 3 + , C 7 H 15 NH 3 + , C 18 H 37 NH 3 + and C 12 H 25 NH 3 + One or more of the group consisting of; A is selected from CH 3 NH 3 + , C 2 H 5 NH 3 + , C 4 H 9 NH 3 + and C 7 H 15 NH 3 + One or more of the group consisting of, M is selected from Pb 2+ and / or Sn 2+ , X is selected from Cl - Br - and I - One or more of the groups consisting of, m is any integer ≥ 2, preferably any integer from 4 to 10.
[0017] Furthermore, a cathode buffer layer is included between the second carrier transport layer and the metal electrode layer; preferably, the thickness of the cathode buffer layer is 10 to 30 nm; preferably, the material of the cathode buffer layer is selected from one or more of the group consisting of 3,3'-(1,3,8,10-tetraanthraquinone[2,1,9-DEF:6,5,10-D'E'F']diisoquinoline-2,9(1H,3H,8H,10H)-diyl)bis(N,N-dimethylpropane-1-amine oxide), ethoxylated polyethyleneimine, poly[3-(6-trimethylammoniumhexyl)thiophene] and tin oxide.
[0018] Furthermore, an anti-reflection layer is provided on the surface of the metal electrode layer away from the crystalline silicon bottom cell; preferably, the thickness of the anti-reflection layer is 50 to 110 nm; preferably, the material of the anti-reflection layer is selected from one or more of the group consisting of magnesium fluoride, calcium fluoride, strontium fluoride, aluminum oxide and aluminum fluoride.
[0019] Further, the first carrier transport layer is a hole transport layer, and the second carrier transport layer is an electron transport layer; preferably, the thickness of the first carrier transport layer is 20 to 50 nm; preferably, the thickness of the second carrier transport layer is 10 to 20 nm; preferably, the material of the first carrier transport layer is selected from one or more of the group consisting of (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine, poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid, molybdenum oxide, nickel oxide, cuprous oxide and cuprous iodide; preferably, the material of the second carrier transport layer is selected from titanium oxide, zinc oxide, C 60 and PCBM.
[0020] Furthermore, the thickness of the metal electrode layer is 800-1000 nm; preferably, the material of the metal electrode layer is selected from one or more of the group consisting of gold, silver and copper.
[0021] Furthermore, the crystalline silicon bottom cell is selected from a TOPCon cell, a HJT cell or an IBC cell.
[0022] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a method for preparing the above-mentioned perovskite / crystalline silicon tandem solar cell provided in the present application, and the preparation method comprises: step S1, preparing a crystalline silicon bottom cell for standby use; step S2, preparing a first carrier transport layer on the surface of one side of the conductive surface of the crystalline silicon bottom cell; step S3, preparing a three-dimensional perovskite active layer on the surface of the first carrier transport layer away from the crystalline silicon bottom cell; step S4, preparing a two-dimensional perovskite active layer on the surface of the three-dimensional perovskite active layer away from the crystalline silicon bottom cell; step S5, coating or spray-depositing a first mixed solution containing a solid organic acid on the surface of the two-dimensional perovskite active layer away from the crystalline silicon bottom cell, and obtaining a surface reconstruction layer after a first drying; step S6, preparing a second carrier transport layer on the surface of the surface reconstruction layer away from the crystalline silicon bottom cell; step S7, preparing a metal electrode layer on the surface of the second carrier transport layer away from the crystalline silicon bottom cell, to obtain a perovskite / crystalline silicon tandem solar cell.
[0023] Furthermore, step S5 further comprises mixing a solid organic acid with a first solvent to obtain a first mixed solution; preferably, in the first mixed solution, the mass concentration of the solid organic acid is 0.5 to 1 mg / mL; preferably, the surface reconstruction layer is prepared by spin coating or scraping, and more preferably, the coating amount of the first mixed solution on the surface of the side of the two-dimensional perovskite active layer away from the crystalline silicon bottom cell is 200 to 1000 mg / cm 2 .
[0024] Furthermore, between step S2 and step S3, the method further includes: mixing the organic polymer with the second solvent to obtain a second mixed liquid, coating or spray-depositing the second mixed liquid on the surface of the first carrier transport layer away from the crystalline silicon bottom battery, and obtaining the stress release layer after a second drying; preferably, in the second mixed liquid, the mass concentration of the organic polymer is 1 to 2 mg / mL; preferably, the stress release layer is prepared by spin coating or blade coating, and more preferably, the coating amount of the second mixed liquid on the surface of the first carrier transport layer away from the crystalline silicon bottom battery is 200 to 1000 mg / cm 2 .
[0025] Further, the first solvent and the second solvent are each independently an alcohol solvent; more preferably, the alcohol solvent is one or more selected from the group consisting of ethanol, isopropanol, n-butanol and isooctyl alcohol.
[0026] Furthermore, the first drying and the second drying are each independently performed at a temperature of 90 to 200° C. and a time of 10 to 20 minutes.
[0027] Furthermore, between step S6 and step S7, the method further includes: preparing a cathode buffer layer on a surface of the second carrier transport layer away from the crystalline silicon bottom cell; preferably, the cathode buffer layer is prepared by magnetron sputtering.
[0028] Furthermore, after step S7, the method further includes: preparing an anti-reflection layer on a surface of the metal electrode layer on a side away from the crystalline silicon bottom cell; more preferably, the anti-reflection layer is prepared by evaporation.
[0029] Furthermore, in step S3, a spin coating method, a blade coating method or a spray deposition method is used for preparation, and a three-dimensional perovskite active layer is obtained after a first annealing treatment; preferably, the temperature of the first annealing treatment is 100 to 160° C., and the time is 10 to 25 minutes.
[0030] Furthermore, in step S4, the two-dimensional perovskite active layer is prepared by spin coating, blade coating or spray deposition, and is subjected to a second annealing treatment; preferably, the temperature of the second annealing treatment is 100 to 130° C., and the time is 10 to 20 minutes.
[0031] Applying the technical solution of the present invention, the present application provides a perovskite / crystalline silicon stacked solar cell, including a crystalline silicon bottom cell, a first carrier transport layer, a three-dimensional perovskite active layer, a two-dimensional perovskite active layer, a surface reconstruction layer, a second carrier transport layer and a metal electrode layer stacked in sequence. The two-dimensional perovskite active layer is arranged on the surface of the three-dimensional perovskite active layer, which can release the internal stress generated by the three-dimensional perovskite active layer during the preparation process, passivate the surface defects of the three-dimensional perovskite active layer, and reduce non-radiative recombination. At the same time, the two-dimensional perovskite active layer can also serve as a protective layer to reduce the direct contact between the three-dimensional perovskite active layer and the external environment, thereby improving the stability and overall performance of the perovskite / crystalline silicon stacked solar cell. A surface reconstruction layer is introduced between the two-dimensional perovskite active layer and the second carrier transport layer, wherein the material of the surface reconstruction layer includes a solid organic acid with a pKa of 3 to 6, and the presence of the solid organic acid can micro-etch the surface of the two-dimensional perovskite active layer, and the PbI exposed on its surface 2 A reaction occurs to remove irregular structures and impurities on its surface, thereby passivating interface defects and reducing non-radiative recombination, thereby improving the photoelectric conversion efficiency of perovskite / crystalline silicon stacked solar cells; at the same time, the solid organic acid can act with the active sites exposed on the surface of the two-dimensional perovskite active layer to reconstruct the crystalline structure and chemical composition of the two-dimensional perovskite material, thereby promoting the deep integration of the two-dimensional perovskite active layer and the three-dimensional perovskite active layer, further releasing the stress accumulated in the three-dimensional perovskite active layer during the preparation process, and converting the surface tensile stress into a slight benign compressive stress, thereby improving the stability of the two-dimensional perovskite active layer and the three-dimensional perovskite active layer, reducing defects, and improving the carrier transmission efficiency, thereby improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0033] Figure 1 A schematic diagram of the stacked structure of a perovskite / crystalline silicon stacked solar cell in one embodiment of the present application is shown;
[0034] Figure 2 A schematic diagram of the stacked structure of a perovskite / crystalline silicon stacked solar cell in another embodiment of the present application is shown;
[0035] Figure 3 A schematic diagram of the stacked structure of a perovskite / crystalline silicon stacked solar cell in another embodiment of the present application is shown.
[0036] The above drawings include the following reference numerals:
[0037] 10. Crystalline silicon bottom cell; 20. First carrier transport layer; 30. Three-dimensional perovskite active layer; 40. Two-dimensional perovskite active layer; 50. Surface reconstruction layer; 60. Second carrier transport layer; 70. Metal electrode layer; 80. Stress release layer; 90. Cathode buffer layer; 11. Anti-reflection layer. DETAILED DESCRIPTION
[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0039] As described in the background art, the existing perovskite film has residual stress that cannot be effectively released, resulting in poor stability and low photoelectric conversion efficiency of perovskite solar cells. In order to solve the above technical problems, the present application provides a perovskite / crystalline silicon tandem solar cell, such as Figure 1 As shown, the perovskite / crystalline silicon stacked solar cell includes a crystalline silicon bottom cell 10, a first carrier transport layer 20, a three-dimensional perovskite active layer 30, a two-dimensional perovskite active layer 40, a surface reconstruction layer 50, a second carrier transport layer 60 and a metal electrode layer 70 which are stacked in sequence, wherein the material of the surface reconstruction layer 50 is a solid organic acid, and the pKa of the solid organic acid is 3 to 6.
[0040] It should be noted that the solid organic acid in the present application refers to an organic acid in a solid state.
[0041] The perovskite / crystalline silicon tandem solar cell provided in this application has the following characteristics: Figure 1The stacked structure shown in the figure, wherein a two-dimensional perovskite active layer 40 is arranged on the surface of the three-dimensional perovskite active layer 30, which can release the internal stress generated by the three-dimensional perovskite active layer 30 during the preparation process, passivate the surface defects of the three-dimensional perovskite active layer 30, and reduce non-radiative recombination. At the same time, the two-dimensional perovskite active layer 40 can also serve as a protective layer to reduce the direct contact between the three-dimensional perovskite active layer 30 and the external environment, thereby improving the stability and overall performance of the perovskite / crystalline silicon stacked solar cell. A surface reconstruction layer 50 is introduced between the two-dimensional perovskite active layer 40 and the second carrier transport layer 60, wherein the material of the surface reconstruction layer 50 includes a solid organic acid with a pKa of 3 to 6, and the presence of the solid organic acid can micro-etch the surface of the two-dimensional perovskite active layer 40, and the PbI exposed on the surface 2 A reaction occurs to remove irregular structures and impurities on its surface, thereby passivating interface defects and reducing non-radiative recombination, thereby improving the photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell; at the same time, the solid organic acid can react with the active sites exposed on the surface of the two-dimensional perovskite active layer 40, so that the crystal structure and chemical composition of the two-dimensional perovskite material are reconstructed, thereby promoting the deep integration of the two-dimensional perovskite active layer 40 and the three-dimensional perovskite active layer 30, and further releasing the stress accumulated in the three-dimensional perovskite active layer 30 during the preparation process, and converting its surface tensile stress into a slight benign compressive stress, thereby improving the stability of the two-dimensional perovskite active layer 40 and the three-dimensional perovskite active layer 30, reducing defects, and improving the carrier transmission efficiency, thereby improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0042] In a preferred embodiment, the solid organic acid includes but is not limited to one or more of the group consisting of monobasic acid, dibasic acid and polybasic acid, and preferably, the pKa of the solid organic acid is 3 to 4. Compared with other types, the use of the above-mentioned types of solid organic acids is conducive to improving the effect of the solid organic acid on the micro-etching of the two-dimensional perovskite active layer 40, thereby being conducive to passivating interface defects, reducing non-radiative recombination, promoting a deeper level of integration of the two-dimensional perovskite active layer 40 with the three-dimensional perovskite active layer 30, and further releasing the stress accumulated in the three-dimensional perovskite active layer 30 during the preparation process, thereby being conducive to improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0043] In order to further improve the micro-etching effect of the solid organic acid on the two-dimensional perovskite active layer 40, thereby further improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell, preferably, the solid organic acid includes but is not limited to one or more of the group consisting of lactic acid, malic acid, tartaric acid, citric acid, oxalic acid and succinic acid.
[0044] In a preferred embodiment, the thickness of the surface reconstruction layer 50 is 20-40 nm. The thickness of the surface reconstruction layer 50 includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the micro-etching effect of the solid organic acid on the two-dimensional perovskite active layer 40, and is also beneficial to inhibiting over-etching, thereby improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0045] In a preferred embodiment, Figure 2 As shown, a stress release layer 80 is also provided between the first carrier transport layer 20 and the three-dimensional perovskite active layer 30. The material of the stress release layer 80 is an organic polymer. The glass transition temperature (Tg) of the organic polymer is 90-250°C and the weight average molecular weight is 100-15000000. Providing the stress release layer 80 between the first carrier transport layer 20 and the three-dimensional perovskite active layer 30 and limiting the glass transition temperature and weight average molecular weight of the organic polymer material to the above range is conducive to reducing the difference in thermal expansion coefficient between the three-dimensional perovskite active layer 30 and the substrate, absorbing and releasing the residual stress generated by the three-dimensional perovskite active layer 30 during the annealing process, and can also serve as an interface modification layer to improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reduce non-radiative recombination, and thus help improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0046] In order to further reduce the difference in thermal expansion coefficients between the three-dimensional perovskite active layer 30 and the substrate, further absorb and release the residual stress generated by the three-dimensional perovskite active layer 30 during the annealing process, further improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reduce non-radiative recombination, and thus further improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cells, preferably, the glass transition temperature of the organic polymer is 100-180°C and the weight-average molecular weight is 1000-60000.
[0047] In a preferred embodiment, the organic polymer has a structure represented by general formula (I), (II) or (III):
[0048]
[0049] Among them, R 1 Including but not limited to hydrogen, C 1 ~C 10 A straight chain or branched alkyl group, or a halogen; n 1 Including but not limited to any integer from 1 to 60; R 2 and R 3 Each independently includes but is not limited to hydrogen, C 1 ~C10 Straight or branched alkyl, C 1 ~C 10 Straight chain or branched chain alkoxy, or halogen; n 2 Including but not limited to any integer from 1 to 30; R 4 and R 5 Each independently includes but is not limited to hydrogen, C 1 ~C 10 A straight chain or branched chain alkyl, or a halogen; R 4 and R 5 Same or different; n 3 Including but not limited to any integer from 1 to 20.
[0050] Compared with other structures, the organic polymer of the structure shown in the above general formula (I), (II) or (III) has a lower Tg, which is beneficial to reduce the difference in thermal expansion coefficient between the three-dimensional perovskite active layer 30 and the substrate, and is beneficial to absorb and release the residual stress generated by the three-dimensional perovskite active layer 30 during the annealing process. It is also beneficial to improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20 and reduce non-radiative recombination. In addition, the benzene ring structure in the structure shown in the above general formula is hydrophobic, and introducing it into the stress release layer 80 can have the effect of internal packaging, which is beneficial to inhibit the three-dimensional perovskite active layer 30 from being eroded by external environments such as moisture and oxygen, and further helps to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0051] In order to further reduce the difference in thermal expansion coefficient between the three-dimensional perovskite active layer 30 and the substrate, further absorb and release the residual stress generated in the three-dimensional perovskite active layer 30 during the annealing process, further improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reduce non-radiative recombination, and further inhibit the three-dimensional perovskite active layer 30 from being corroded by external environments such as moisture and oxygen, thereby further improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell, preferably, R 1 Including but not limited to hydrogen, C 5 ~C 8 A straight or branched alkyl group, or F, more preferably hydrogen, n 1 Including but not limited to any integer between 40 and 50; preferably, R 2 Including but not limited to C 1 ~C 8 The straight chain alkoxy group, R 3 With R 2 Same, n 2 Including but not limited to any integer between 20 and 25; preferably, R 4 Including but not limited to C 1 ~C8 The branched alkyl group, R 5 With R 4 Same, n 3 Including but not limited to any integer between 10 and 15; more preferably, R 2 and R 3 More preferably, R 4 With R 5 Both
[0052] In order to further reduce the difference in thermal expansion coefficient between the three-dimensional perovskite active layer 30 and the substrate, further absorb and release the residual stress generated by the three-dimensional perovskite active layer 30 during the annealing process, further improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reduce non-radiative recombination, and further inhibit the three-dimensional perovskite active layer 30 from being corroded by external environments such as moisture and oxygen, thereby further improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell, preferably, the organic polymer includes but is not limited to polystyrene (PS), poly[(meta-phenylene vinylene)-co-(2,5-dioctyloxy-p-phenylene vinylene)] (PmPV) and poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-B:3,4-B']dithiophene-2,6-diyl]] (PCPDTBT) One or more of the group consisting of. Among them, the structures of PS, PmPV and PCPDTBT are as follows:
[0053]
[0054] In a preferred embodiment, the thickness of the stress release layer 80 is 10 to 20 nm. The thickness of the stress release layer 80 includes but is not limited to the above range. Limiting it within the above range is conducive to further releasing the internal stress of the three-dimensional perovskite active layer 30, improving the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reducing non-radiative recombination, and also helping to inhibit the three-dimensional perovskite active layer 30 from being eroded by external environments such as moisture and oxygen, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0055] In a preferred embodiment, the thickness of the three-dimensional perovskite active layer 30 is 300-500nm, and the band gap is 1.78-2.03eV. The thickness and band gap of the three-dimensional perovskite active layer 30 include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the light absorption efficiency of the three-dimensional perovskite active layer 30, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0056] In a preferred embodiment, the thickness of the two-dimensional perovskite active layer 40 is 100 to 300 nm, and the band gap is 1.4 to 2.5 eV. The thickness and band gap of the two-dimensional perovskite active layer 40 include but are not limited to the above ranges. Limiting it within the above range is conducive to improving the light absorption efficiency of the two-dimensional perovskite active layer 40, and is conducive to improving its energy level matching with the three-dimensional perovskite active layer 30. At the same time, it is conducive to reducing the direct contact between the three-dimensional perovskite active layer 30 and the external environment, and is conducive to releasing the internal stress generated by the three-dimensional perovskite active layer 30 during the preparation process, passivating its surface defects, thereby improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0057] In order to further improve the light absorption efficiency of the three-dimensional perovskite active layer 30 and further improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell, in a preferred embodiment, the material of the three-dimensional perovskite active layer 30 is ABX 3 , where A includes but is not limited to CH 3 NH 3 + NH=CHNH 3 + and Cs + One or more of the group consisting of; B includes but is not limited to Pb 2+ and / or Sn 2+ ; X includes but is not limited to Cl - Br - and I - One or more of the groups.
[0058] In a preferred embodiment, the material of the two-dimensional perovskite active layer 40 is L 2 A m-1 M m X 3m+1 , where L includes but is not limited to C 4 H 9 NH 3 + , C 7 H 15 NH 3 + , C 18 H 37 NH 3 + and C 12 H 25 NH 3 + One or more of the group consisting of; A includes but is not limited to CH 3 NH 3 + , C2 H 5 NH 3 + , C 4 H 9 NH 3 + and C 7 H 15 NH 3 + One or more of the group consisting of, M including but not limited to Pb 2+ and / or Sn 2+ , X includes but is not limited to Cl - Br - and I - One or more of the group consisting of, m is any integer ≥ 2, preferably any integer from 4 to 10. Compared with other materials, the use of the above materials is conducive to improving the light absorption efficiency of the two-dimensional perovskite active layer 40, and is conducive to improving its energy level matching with the three-dimensional perovskite active layer 30, thereby helping to improve the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0059] In a preferred embodiment, Figure 3 As shown, a cathode buffer layer 90 is further included between the second carrier transport layer 60 and the metal electrode layer 70. The cathode buffer layer 90 is provided to improve the carrier transport efficiency, and is also beneficial to protect the three-dimensional perovskite active layer 30 and the two-dimensional perovskite active layer 40, thereby improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0060] In a preferred embodiment, the thickness of the cathode buffer layer 90 is 10 to 30 nm. The thickness of the cathode buffer layer 90 includes but is not limited to the above range, and limiting it within the above range is conducive to improving the carrier transmission efficiency, and is conducive to protecting the three-dimensional perovskite active layer 30 and the two-dimensional perovskite active layer 40, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0061] In a preferred embodiment, the material of the cathode buffer layer 90 includes, but is not limited to, one or more of the group consisting of 3,3'-(1,3,8,10-tetraanthraquinone [2,1,9-DEF:6,5,10-D'E'F'] diisoquinoline-2,9 (1H,3H,8H,10H)-diyl) bis (N,N-dimethylpropane-1-amine oxide) (PDINO), ethoxylated polyethyleneimine (PEIE), poly [3-(6-trimethylammoniumhexyl) thiophene] (P3TMAHT) and tin oxide. Compared with other types, the use of the above-mentioned types of cathode buffer layer 90 materials is conducive to improving the carrier transmission efficiency, thereby improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon tandem solar cell.
[0062] In a preferred embodiment, Figure 3 As shown, the metal electrode layer 70 is further provided with an anti-reflection layer 11 on one side of the surface away from the crystalline silicon bottom cell 10. The provision of the anti-reflection layer 11 is beneficial to reducing the reflection loss of light, thereby facilitating the improvement of the photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0063] In order to further reduce the reflection loss of light and thus further improve the photoelectric conversion efficiency of the perovskite / crystalline silicon tandem solar cell, preferably, the material of the anti-reflection layer 11 includes but is not limited to one or more of the group consisting of magnesium fluoride, calcium fluoride, strontium fluoride, aluminum oxide and aluminum fluoride.
[0064] In a preferred embodiment, the thickness of the anti-reflection layer 11 is 50-110 nm. The thickness of the anti-reflection layer 11 includes but is not limited to the above range, which is beneficial to reducing the reflection loss of light and improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0065] The perovskite / crystalline silicon tandem solar cell provided in the present application may be a perovskite / crystalline silicon tandem solar cell with an inverted structure (pin). In a preferred embodiment, the first carrier transport layer 20 is a hole transport layer, and the second carrier transport layer 60 is an electron transport layer.
[0066] In a preferred embodiment, the thickness of the first carrier transport layer 20 is 20 to 50 nm. The thickness of the first carrier transport layer 20 includes but is not limited to the above range, and limiting it within the above range is conducive to improving the carrier collection efficiency of the first carrier transport layer 20, and is conducive to reducing the recombination of carriers, thereby facilitating the improvement of the carrier transport efficiency, and further facilitating the improvement of the photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0067] In order to improve the carrier transport efficiency of the first carrier transport layer 20, in a preferred embodiment, the material of the first carrier transport layer 20 includes but is not limited to (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA), poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid (PEDOT:PSS), molybdenum oxide, nickel oxide, cuprous oxide and cuprous iodide. One or more of the group consisting of.
[0068] In a preferred embodiment, the thickness of the second carrier transport layer 60 is 10 to 20 nm. The thickness of the second carrier transport layer 60 includes but is not limited to the above range, and limiting it within the above range is conducive to improving the carrier collection efficiency of the second carrier transport layer 60, and is conducive to reducing the recombination of carriers, thereby facilitating the improvement of the carrier transport efficiency, and further facilitating the improvement of the photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0069] In order to improve the carrier transport efficiency of the second carrier transport layer 60, in a preferred embodiment, the material of the second carrier transport layer 60 includes but is not limited to titanium oxide, zinc oxide, C 60 One or more of the group consisting of (footballene) and PCBM (fullerene derivative).
[0070] In a preferred embodiment, the thickness of the metal electrode layer 70 is 800-1000 nm. The thickness of the metal electrode layer 70 includes but is not limited to the above range, and limiting it within the above range is conducive to improving the conductivity and stability of the metal electrode layer 70, thereby helping to improve the photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0071] In order to improve the conductivity and stability of the metal electrode layer 70, in a preferred embodiment, the material of the metal electrode layer 70 includes but is not limited to one or more of the group consisting of gold, silver and copper.
[0072] In a preferred embodiment, the crystalline silicon bottom cell 10 includes but is not limited to a TOPCon cell, a HJT cell or an IBC cell. Compared with other types, the use of the above-mentioned type of crystalline silicon bottom cell 10 is conducive to improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon tandem solar cell.
[0073] The second aspect of the present application also provides a method for preparing the above-mentioned perovskite / crystalline silicon stacked solar cell provided by the present application, and the preparation method comprises: step S1, preparing a crystalline silicon bottom cell 10 for standby use; step S2, preparing a first carrier transport layer 20 on a side surface of the conductive surface of the crystalline silicon bottom cell 10; step S3, preparing a three-dimensional perovskite active layer 30 on a side surface of the first carrier transport layer 20 away from the crystalline silicon bottom cell 10; step S4, preparing a three-dimensional perovskite active layer 30 on a side surface of the three-dimensional perovskite active layer 30 away from the crystalline silicon bottom cell 10. to the two-dimensional perovskite active layer 40; step S5, coating or spraying a first mixed solution containing a solid organic acid on a surface of the two-dimensional perovskite active layer 40 away from the crystalline silicon bottom battery 10, and obtaining a surface reconstruction layer 50 after a first drying; step S6, preparing a second carrier transport layer 60 on a surface of the surface reconstruction layer 50 away from the crystalline silicon bottom battery 10; step S7, preparing a metal electrode layer 70 on a surface of the second carrier transport layer 60 away from the crystalline silicon bottom battery 10, to obtain a perovskite / crystalline silicon stacked solar cell.
[0074] The above preparation method can obtain Figure 1 The perovskite / crystalline silicon tandem solar cell with the stacked structure shown can prepare a two-dimensional perovskite active layer 40 on the surface of the three-dimensional perovskite active layer 30 through step S4. The introduction of the two-dimensional perovskite active layer 40 can release the internal stress generated by the three-dimensional perovskite active layer 30 during the preparation process, passivate the surface defects of the three-dimensional perovskite active layer 30, and reduce non-radiative recombination. At the same time, the two-dimensional perovskite active layer 40 can also serve as a protective layer to reduce the direct contact between the three-dimensional perovskite active layer 30 and the external environment, thereby improving the stability and overall performance of the perovskite / crystalline silicon tandem solar cell. The surface reconstruction layer 50 containing solid organic acid can be set in the stacked structure of the perovskite / crystalline silicon tandem solar cell through step S5; wherein the presence of the solid organic acid can micro-etch the surface of the two-dimensional perovskite active layer 40, and the PbI exposed on its surface 2 A reaction occurs to remove irregular structures and impurities on its surface, thereby passivating interface defects and reducing non-radiative recombination, thereby improving the photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell; at the same time, the solid organic acid can react with the active sites exposed on the surface of the two-dimensional perovskite active layer 40, so that the crystalline structure and chemical composition of the two-dimensional perovskite material are reconstructed, thereby promoting the deep integration of the two-dimensional perovskite active layer 40 and the three-dimensional perovskite active layer 30, further releasing the stress accumulated in the three-dimensional perovskite active layer 30 during the preparation process, and converting the surface tensile stress into a slight benign compressive stress, thereby improving the stability of the two-dimensional perovskite active layer 40 and the three-dimensional perovskite active layer 30, reducing defects, and improving the carrier transmission efficiency, thereby improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0075] In order to improve the dispersibility of the solid organic acid and facilitate obtaining the surface reconstruction layer 50, in a preferred embodiment, step S5 further includes mixing the solid organic acid with a first solvent to obtain a first mixed solution.
[0076] In a preferred embodiment, in the first mixed solution, the mass concentration of the solid organic acid is 0.5-1 mg / mL. The mass concentration of the solid organic acid includes but is not limited to the above range, and limiting it within the above range is conducive to improving the micro-etching effect of the solid organic acid on the two-dimensional perovskite active layer 40, and is also conducive to inhibiting over-etching, thereby facilitating improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0077] In a preferred embodiment, the surface reconstruction layer 50 is prepared by spin coating or blade coating. More preferably, the coating amount of the first mixed solution on the surface of the two-dimensional perovskite active layer 40 away from the crystalline silicon bottom cell 10 is 200-1000 mg / cm 2 Compared with other ranges, limiting the coating amount of the first mixed solution on the surface of the two-dimensional perovskite active layer 40 to the above range is conducive to obtaining a surface reconstruction layer 50 with a suitable thickness, thereby facilitating the micro-etching effect of the solid organic acid on the two-dimensional perovskite active layer 40, and further facilitating the improvement of the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0078] In a preferred embodiment, between step S2 and step S3, the following step is further included: mixing the organic polymer with the second solvent to obtain a second mixed solution, coating or spraying the second mixed solution on the surface of the first carrier transport layer 20 away from the crystalline silicon bottom cell 10, and obtaining the stress release layer 80 after a second drying. The above method is convenient for coating or spraying the second solution containing the organic polymer on the surface of the first carrier transport layer 20 to obtain the stress release layer 80, such as Figure 2 As shown, it is beneficial to reduce the difference in thermal expansion coefficients between the three-dimensional perovskite active layer 30 and the substrate, to absorb and release the residual stress generated in the three-dimensional perovskite active layer 30 during the annealing process, to improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, and to reduce non-radiative recombination. At the same time, it is also beneficial to inhibit the three-dimensional perovskite active layer 30 from being eroded by external environments such as moisture and oxygen, thereby improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cells.
[0079] In a preferred embodiment, in the second mixed solution, the mass concentration of the organic polymer is 1 to 2 mg / mL. The mass concentration of the organic polymer includes but is not limited to the above range, and limiting it within the above range is conducive to reducing the difference in thermal expansion coefficient between the three-dimensional perovskite active layer 30 and the substrate, absorbing and releasing the residual stress generated by the three-dimensional perovskite active layer 30 during the annealing process, improving the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, and reducing non-radiative recombination, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0080] In a preferred embodiment, the stress release layer 80 is prepared by spin coating or scraping, and more preferably, the coating amount of the second mixed liquid on the surface of the first carrier transport layer 20 away from the crystalline silicon bottom cell 10 is 200-1000 mg / cm 2 Compared with other ranges, limiting the coating amount of the second solution on the surface of the first carrier transport layer 20 to the above range is conducive to obtaining a stress release layer 80 with an appropriate thickness, thereby facilitating the release of the internal stress of the three-dimensional perovskite active layer 30, improving the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reducing non-radiative recombination, and also helping to inhibit the three-dimensional perovskite active layer 30 from being eroded by external environments such as moisture and oxygen, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0081] In order to improve the dispersibility of the solid organic acid and the organic polymer and to obtain a more evenly dispersed first mixed liquid and a second mixed liquid, in a preferred embodiment, the first solvent and the second solvent are each independently an alcohol solvent; more preferably, the alcohol solvent includes but is not limited to one or more of the group consisting of ethanol, isopropanol, n-butanol and isooctyl alcohol.
[0082] In order to improve the removal efficiency of the solvent in the surface reconstruction layer 50 and the stress release layer 80, in a preferred embodiment, the temperature of the first drying and the second drying are independently 90-200°C and the time is 10-20 minutes.
[0083] In a preferred embodiment, between step S6 and step S7, the process further includes: preparing a cathode buffer layer 90 on the surface of the second carrier transport layer 60 away from the crystalline silicon bottom cell 10; preferably, the cathode buffer layer 90 is prepared by magnetron sputtering. The above method is conducive to obtaining a cathode buffer layer 90 with better film quality, such as Figure 3 As shown, it is beneficial to improve the carrier transmission efficiency, protect the three-dimensional perovskite active layer 30 and the two-dimensional perovskite active layer 40, and further improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0084] In a preferred embodiment, after step S7, the process further includes: preparing an anti-reflection layer 11 on the surface of the metal electrode layer 70 away from the crystalline silicon bottom cell 10; preferably, the anti-reflection layer 11 is prepared by evaporation. The above method is conducive to obtaining an anti-reflection layer 11 with better film quality, such as Figure 3 As shown, this is beneficial to reducing the reflection loss of light, and further beneficial to improving the photoelectric conversion efficiency of the perovskite / crystalline silicon tandem solar cell.
[0085] In a preferred embodiment, in step S3, a spin coating method, a blade coating method or a spray deposition method is used for preparation, and a three-dimensional perovskite active layer 30 is obtained after a first annealing treatment. The above preparation method is conducive to improving the crystallinity of the three-dimensional perovskite active layer 30, reducing its surface defects, and obtaining a three-dimensional perovskite active layer 30 with better film quality, thereby improving the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0086] In order to further improve the crystallinity of the three-dimensional perovskite active layer 30, further reduce its surface defects, and further improve its thermal stability and chemical stability, preferably, the temperature of the first annealing treatment is 100-160° C. and the time is 10-25 min.
[0087] In a preferred embodiment, in step S4, a spin coating method, a blade coating method or a spray deposition method is used for preparation, and after a second annealing treatment, a two-dimensional perovskite active layer 40 is obtained. The above preparation method is conducive to improving the crystallinity of the two-dimensional perovskite active layer 40, reducing its surface defects, and obtaining a two-dimensional perovskite active layer 40 with better film quality, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0088] In order to further improve the crystallinity of the two-dimensional perovskite active layer 40, further reduce its surface defects, and further improve its thermal stability and chemical stability, preferably, the temperature of the second annealing treatment is 100-130° C., and the time is 10-20 min.
[0089] In a preferred embodiment, in step S2, the first carrier transport layer 20 is prepared by evaporation, doctor blade coating, spray deposition or inkjet printing; in step S6, the second carrier transport layer 60 is prepared by evaporation, doctor blade coating, spray deposition or inkjet printing; in step S7, the metal electrode layer 70 is prepared by screen printing or evaporation. Compared with other methods, the above methods are conducive to improving the film forming properties and uniformity of each film layer, and can obtain a higher quality film layer.
[0090] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0091] Example 1
[0092] A method for preparing a perovskite / crystalline silicon tandem solar cell comprises the following steps:
[0093] (1) Preparation of crystalline silicon bottom cell 10: Cleaning and texturing on N-type silicon substrate, first pre-cleaning with 10wt% NaOH at 78°C for 50s; then cleaning with NaOH, NaOH at 75°C for 50s; 2 SiO 3 The surface of one side of the silicon wafer was textured with a mixed solution of 1% ethanol and isopropyl alcohol (IPA) for 35 minutes to obtain a textured silicon wafer. On the surface of the silicon wafer facing away from the textured surface after the textured process, The Ag electrode layer with a thickness of 1 μm was obtained by evaporation at a deposition rate of 1 μm. The intrinsic amorphous silicon film and the doped amorphous silicon film were sequentially deposited on the surface of the side of the silicon wafer away from the Ag electrode layer after the texturing by using a plasma enhanced chemical vapor deposition (PECVD) device (Anhui Beiyike, PECVD-III-500A-D210) to form a PN junction. The preheating time of the PECVD chamber was set to 30 min, and H was introduced. 2 The silicon substrate was cleaned by sputtering for 10 min, and then H was introduced into the PECVD equipment. 2 、SiH 4 , PH 3 and B 2 H 6 The amorphous silicon film is deposited by ignition; the treated film is placed in a double-sided heterojunction TCO magnetron sputtering coating device (Hunan Red Sun Photoelectric Technology Co., Ltd., RSP-8000) to deposit a TCO transparent conductive oxide film, and the vacuum degree is set to 8.9 Pa, the sputtering power is 45 W, and the sputtering time is 900 min to obtain a HJT battery. The stacked structure of the HJT battery is represented as: back Ag / TCO / p-polysilicon / intrinsic amorphous silicon / n-Si / intrinsic amorphous silicon / n-polysilicon / TCO;
[0094] (2) Preparation of hole transport layer: 100 mL of NiO with a mass concentration of 0.3 mg / mL was added x The aqueous solution was spin-coated at a speed of 4000 rpm on one side of the TCO transparent conductive oxide film of the crystalline silicon bottom cell 10 provided in step (1) for 30 seconds, and then placed on a hot plate at 100° C. for annealing for 10 minutes to obtain a NiO film with a thickness of 20 nm. x layer;
[0095] (3) Preparation of stress release layer 80: 1.5 mg PmPV (purchased from Merck Sigma-Aldrich, CAS No.: 184431-56-9, Tg of 120° C., weight average molecular weight of 10,000, compound represented by general formula (II), R 2 With R 3 All octyloxy) were dissolved in 1 mL of isopropanol to obtain a mixed solution at 500 mg / cm 2 The mixed solution is spin-coated on the NiO prepared in step (2) x The layer is formed on the surface of one side away from the crystalline silicon bottom cell 10, wherein the rotation speed of the spin coating is 8000 rpm, and after the spin coating for 20 seconds, it is transferred to a 130° C. oven and dried for 15 minutes to obtain a stress release layer 80 with a thickness of 10 nm;
[0096] (4) Preparation of three-dimensional perovskite active layer 30: PbI 2 , MAI (methylamine iodide), FABr (formamidine bromide) and CsBr powders are dispersed in a mixed solvent of 5 mL N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (the volume ratio of DMF to DMSO is 5:2) in a molar ratio of 5:4:5:1, and stirred for 5 hours to prepare a perovskite precursor solution; the perovskite precursor solution is spin-coated on the side of the stress release layer 80 prepared in step (3) away from the crystalline silicon bottom cell 10, first spin-coated at 3000 rpm for 20 seconds, then transferred to a heating plate at 100°C, annealed for 10 minutes, and then 50 μL of chlorobenzene is added and spin-coated at 5000 rpm for 30 seconds; then it is transferred to a heating plate at 110°C and annealed for 15 minutes to obtain a (CsBr) with a thickness of 500 nm. 0.1 FA 0.5 MA 0.0.4 )Pb(I 0.8 Br 0.2 ) 3 Perovskite active layer Three-dimensional perovskite active layer 30;
[0097] (5) Preparation of two-dimensional perovskite active layer 40: butyl ammonium acetate (BAAc, CAS No.: 1641-36-7), MAI and PbI 2 Disperse in a mixed solvent of 5 mL DMF and DMSO (the volume ratio of DMF to DMSO is 4:1) at a molar ratio of 0.31:0.47:0.31, stir for 2 hours, and prepare a two-dimensional perovskite precursor solution; spin-coat the two-dimensional perovskite precursor solution on the surface of the three-dimensional perovskite active layer 30 prepared in step (4) away from the crystalline silicon bottom battery 10 at a speed of 4000 rpm for 20 seconds, then transfer to a heating plate at 100° C., anneal for 10 minutes, and obtain a two-dimensional perovskite active layer 40 with a thickness of 300 nm;
[0098] (6) Preparation of surface reconstruction layer 50: 4 mg of lactic acid (CAS No.: 50-21-5, pKa: 3.86) was dissolved in 5 mL of isopropanol to obtain a mixed solution at a concentration of 500 mg / cm 2 The mixed solution is spin-coated on the surface of the two-dimensional perovskite active layer 40 prepared in step (5) on the side away from the crystalline silicon bottom cell 10, wherein the spin-coating speed is 6000 rpm, and after spin-coating for 30 seconds, it is transferred to a 90° C. oven and dried for 10 minutes to obtain a surface reconstruction layer 50 with a thickness of 20 nm;
[0099] (7) Preparation of electron transport layer: The surface reconstruction layer 50 prepared in step (6) is disposed on a side away from the crystalline silicon bottom cell 10. The deposition rate was 20 nm. 60 layer;
[0100] (8) Preparation of cathode buffer layer 90: SnO 2 The C prepared in step (7) is sputtered and deposited 60 The SnO layer with a thickness of 20 nm is obtained on the surface of the side away from the crystalline silicon bottom cell 10. 2 layer, wherein the vacuum degree is 4.8 Pa, the sputtering power is 35 W, the sputtering time is 60 min, and the argon gas flow rate is 800 sccm;
[0101] (9) Preparation of metal electrode layer 70: The SnO prepared in step (8) 2 The layer is away from the side surface of the crystalline silicon bottom cell 10, so that The Ag electrode layer with a thickness of 1000 nm was obtained by evaporation at a deposition rate of .
[0102] (10) Preparation of anti-reflection layer 11: The Ag electrode layer prepared in step (9) is placed on the side away from the crystalline silicon bottom cell 10. The MgF with a thickness of 100 nm was obtained by evaporation at a deposition rate of 2 layer.
[0103] The laminated structure of the perovskite / crystalline silicon laminated solar cell prepared in this embodiment is as follows: Figure 3 shown.
[0104] Example 2
[0105] The difference from Example 1 is that in step (6), the mass concentration of lactic acid in the mixed solution is 0.5 mg / mL, and the remaining steps are the same as Example 1.
[0106] Example 3
[0107] The difference from Example 1 is that in step (6), the mass concentration of lactic acid in the mixed solution is 1 mg / mL, and the remaining steps are the same as in Example 1.
[0108] Example 4
[0109] The difference from Example 1 is that in step (6), the mass concentration of lactic acid in the mixed solution is 0.1 mg / mL, and the remaining steps are the same as in Example 1.
[0110] Example 5
[0111] The difference from Example 1 is that in step (6), the coating amount of the mixed solution on the surface of the two-dimensional perovskite active layer 40 prepared in step (5) is 1000 mg / cm 2 , the remaining steps are the same as those in Example 1.
[0112] Example 6
[0113] The difference from Example 1 is that in step (6), the coating amount of the mixed solution on the surface of the two-dimensional perovskite active layer 40 prepared in step (5) is 80 mg / cm 2 , the remaining steps are the same as those in Example 1.
[0114] Example 7
[0115] The difference from Example 1 is that in step (6), an equal amount of malic acid (CAS No.: 6915-15-7, pKa: 3.4) is used to replace lactic acid, and the remaining steps are the same as those in Example 1.
[0116] Example 8
[0117] The difference from Example 1 is that in step (6), an equal amount of citric acid (CAS No.: 77-92-9, pKa: 3.1) is used to replace lactic acid, and the remaining steps are the same as Example 1.
[0118] Example 9
[0119] The difference from Example 1 is that step (3) is omitted and the NiO obtained in step (2) is directly x A three-dimensional perovskite active layer 30 is prepared on a surface of the layer away from the surface of the crystalline silicon bottom cell 10, and the remaining steps are the same as those in Example 1.
[0120] The stress release layer 80 is not introduced into the perovskite / crystalline silicon tandem solar cell prepared in this embodiment.
[0121] Example 10
[0122] The difference from Example 1 is that in step (3), an equal amount of PS (purchased from MacLean, CAS No.: 9003-53-6, Tg of 105°C, weight average molecular weight of 6000, compound represented by general formula (I), R 1 The remaining steps are the same as those in Example 1.
[0123] Embodiment 11
[0124] The difference from Example 1 is that in step (3), an equal amount of PCPDTBT (purchased from Merck Sigma-Aldrich, CAS No.: 920515-34-0, Tg is 180°C, weight average molecular weight is 30000, the compound represented by general formula (III), R 5 and R 4 Both ) replaced PmPV, and the remaining steps were the same as in Example 1.
[0125] Example 12
[0126] The difference from Example 1 is that in step (3), the mass concentration of PmPV in the mixed solution is 1 mg / mL, and the remaining steps are the same as Example 1.
[0127] Embodiment 13
[0128] The difference from Example 1 is that in step (3), the mass concentration of PmPV in the mixed solution is 2 mg / mL, and the remaining steps are the same as Example 1.
[0129] Embodiment 14
[0130] The difference from Example 1 is that in step (3), the mass concentration of PmPV in the mixed solution is 0.8 mg / mL, and the remaining steps are the same as in Example 1.
[0131] Embodiment 15
[0132] The difference from Example 1 is that in step (3), the mixed solution is NiO prepared in step (2) x The coating amount on the surface of the layer is 200 mg / cm 2 , the remaining steps are the same as those in Example 1.
[0133] Example 16
[0134] The difference from Example 1 is that in step (3), the mixed solution is NiO prepared in step (2) x The coating amount on the surface of the layer is 70 mg / cm 2 , the remaining steps are the same as those in Example 1.
[0135] Embodiment 17
[0136] The difference from Example 1 is that step (8) is omitted and the C obtained in step (7) is directly used. 60 A metal electrode layer 70 is prepared on a surface of the layer away from the surface of the crystalline silicon bottom cell 10 , and the remaining steps are the same as those in Example 1.
[0137] The cathode buffer layer 90 is not introduced into the perovskite / crystalline silicon tandem solar cell prepared in this embodiment.
[0138] Embodiment 18
[0139] The difference from Example 1 is that step (10) is omitted, and the stacked structure obtained in step (9) is used as the perovskite / crystalline silicon stacked solar cell of this embodiment, and the remaining steps are the same as those of Example 1.
[0140] The anti-reflection layer 11 is not introduced into the perovskite / crystalline silicon tandem solar cell prepared in this embodiment.
[0141] Embodiment 19
[0142] The difference from Example 1 is that in step (4), the annealing temperature is 160° C. and the time is 25 min. The remaining steps are the same as Example 1.
[0143] Embodiment 20
[0144] The difference from Example 1 is that in step (4), the annealing temperature is 80° C. and the time is 30 min. The remaining steps are the same as Example 1.
[0145] Embodiment 21
[0146] The difference from Example 1 is that in step (5), the annealing temperature is 130° C. and the time is 20 min. The remaining steps are the same as Example 1.
[0147] Embodiment 22
[0148] The difference from Example 1 is that in step (5), the annealing temperature is 90° C. and the time is 30 min. The remaining steps are the same as Example 1.
[0149] Comparative Example 1
[0150] The difference from Example 1 is that step (6) is omitted, and an electron transport layer is directly prepared on the surface of the two-dimensional perovskite active layer 40 prepared in step (5) away from the surface of the crystalline silicon bottom cell 10, and the remaining steps are the same as in Example 1.
[0151] The surface reconstruction layer 50 is not introduced into the perovskite / crystalline silicon tandem solar cell prepared in this comparative example.
[0152] Comparative Example 2
[0153] The difference from Example 1 is that step (6) is omitted, an equal amount of lactic acid is added as an additive to the two-dimensional perovskite active layer 40 in step (5), and the remaining steps are the same as in Example 1.
[0154] Comparative Example 3
[0155] The difference from Example 1 is that step (5) is omitted, and a surface reconstruction layer 50 is directly prepared on the surface of the three-dimensional perovskite active layer 30 prepared in step (4) which is away from the surface of the crystalline silicon bottom cell 10, and the remaining steps are the same as in Example 1.
[0156] The two-dimensional perovskite active layer 40 is not introduced into the perovskite / crystalline silicon tandem solar cell prepared in this comparative example.
[0157] The photovoltaic performance of the perovskite / crystalline silicon stacked solar cells prepared in all the above embodiments and comparative examples of the present application was tested. The effective area of the device was 1 cm 2 , at 100mW / cm 2 The JV curve of the perovskite / crystalline silicon tandem solar cell was tested under simulated sunlight conditions using a solar simulator (Newport, Oriel Sol3A Class AAA) and a Keithley 2400 digital source meter. The stability test conditions were as follows: the perovskite / crystalline silicon tandem solar cells prepared in all the above embodiments and comparative examples were placed in air (5-10% RH) at 100 mW / cm 2 The test results are shown in Table 1 below.
[0158] Table 1
[0159]
[0160] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0161] By comparing Examples 1, 7 and 8 and Comparative Examples 1 and 2, it can be seen that compared with other types, the solid organic acid of the type defined in the present application is used as the material of the surface reconstruction layer 50, and it is arranged between the two-dimensional perovskite active layer 40 and the second carrier transport layer 60. The presence of the solid organic acid can, on the one hand, micro-etch the surface of the two-dimensional perovskite active layer 40, and on the other hand, the PbI 2On the one hand, it can react to remove irregular structures and impurities on its surface, passivate interface defects, and reduce non-radiative recombination; on the other hand, it can also react with the active sites exposed on the surface of the two-dimensional perovskite active layer 40, reconstruct the crystalline structure and chemical composition of the two-dimensional perovskite material, promote the deep integration of the two-dimensional perovskite active layer 40 and the three-dimensional perovskite active layer 30, further release the stress accumulated in the three-dimensional perovskite active layer 30 during the preparation process, and convert the surface tensile stress into a slight benign compressive stress, thereby improving the stability of the two-dimensional perovskite active layer 40 and the three-dimensional perovskite active layer 30, reducing defects, and improving the carrier transmission efficiency, thereby improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0162] By comparing Example 1 and Comparative Example 3, it can be seen that the two-dimensional perovskite active layer 40 is arranged on the surface of the three-dimensional perovskite active layer 30. On the one hand, it can release the internal stress generated by the three-dimensional perovskite active layer 30 during the preparation process, passivate the surface defects of the three-dimensional perovskite active layer 30, and reduce non-radiative recombination. On the other hand, it can also serve as a protective layer to reduce the direct contact between the three-dimensional perovskite active layer 30 and the external environment, thereby improving the stability and photoelectric conversion efficiency of the perovskite / crystalline silicon stacked solar cell.
[0163] By comparing Examples 1 to 4, it can be seen that, compared with other ranges, limiting the mass concentration of the solid organic acid within the above-mentioned range of the present application is beneficial to improving the micro-etching effect of the solid organic acid on the two-dimensional perovskite active layer 40, and is also beneficial to inhibiting excessive etching, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0164] By comparing Examples 1, 5 and 6, it can be seen that, compared with other ranges, limiting the coating amount of the first mixed liquid on the surface of the two-dimensional perovskite active layer 40 to within the above range is beneficial to obtaining a surface reconstruction layer 50 of appropriate thickness, thereby helping to improve the micro-etching effect of the solid organic acid on the two-dimensional perovskite active layer 40, helping to inhibit excessive etching, and further helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0165] By comparing Examples 1, 9 to 11, it can be seen that introducing a stress release layer 80 between the first carrier transport layer 20 and the three-dimensional perovskite active layer 30 and using the above-mentioned specific type of material defined in the present application is beneficial to reducing the difference in thermal expansion coefficients between the three-dimensional perovskite active layer 30 and the substrate, and is beneficial to absorbing and releasing the residual stress generated in the three-dimensional perovskite active layer 30 during the annealing process. At the same time, it can also serve as an interface modification layer to improve the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reduce non-radiative recombination, and thus help to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0166] By comparing Examples 1 and 12 to 14, it can be seen that, compared with other ranges, limiting the mass concentration of the organic polymer within the above range is beneficial to reducing the difference in thermal expansion coefficients between the three-dimensional perovskite active layer 30 and the substrate, absorbing and releasing the residual stress generated in the three-dimensional perovskite active layer 30 during the annealing process, improving the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, and reducing non-radiative recombination, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cells.
[0167] By comparing Examples 1, 15 and 16, it can be seen that, compared with other ranges, limiting the coating amount of the second solution on the surface of the first carrier transport layer 20 to the above range is beneficial to obtaining a stress release layer 80 with an appropriate thickness, thereby facilitating the release of the internal stress of the three-dimensional perovskite active layer 30, improving the interface defects between the three-dimensional perovskite active layer 30 and the first carrier transport layer 20, reducing non-radiative recombination, and also helping to inhibit the three-dimensional perovskite active layer 30 from being eroded by external environments such as moisture and oxygen, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cells.
[0168] By comparing Examples 1 and 17, it can be seen that the provision of the cathode buffer layer 90 is beneficial to improving the carrier transmission efficiency, and is also beneficial to protecting the three-dimensional perovskite active layer 30 and the two-dimensional perovskite active layer 40, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0169] By comparing Examples 1 and 18, it can be seen that the provision of the anti-reflection layer 11 is beneficial to reducing the reflection loss of light, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0170] By comparing Examples 1, 19 and 20, it can be seen that, compared with other ranges, limiting the temperature and time of the first annealing treatment within the above-mentioned range of the present application is beneficial to improving the crystallinity of the three-dimensional perovskite active layer 30, reducing its surface defects, and improving its thermal stability and chemical stability, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0171] By comparing Examples 1, 21 and 22, it can be seen that, compared with other ranges, limiting the temperature and time of the second annealing treatment within the above-mentioned range of the present application is beneficial to improving the crystallinity of the two-dimensional perovskite active layer 40, reducing its surface defects, and improving the thermal stability and chemical stability of the two-dimensional perovskite active layer 40, thereby helping to improve the photoelectric conversion efficiency and stability of the perovskite / crystalline silicon stacked solar cell.
[0172] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A perovskite / crystalline silicon tandem solar cell, characterized in that: The perovskite / crystalline silicon stacked solar cell comprises a crystalline silicon bottom cell (10), a first carrier transport layer (20), a three-dimensional perovskite active layer (30), a two-dimensional perovskite active layer (40), a surface reconstruction layer (50), a second carrier transport layer (60) and a metal electrode layer (70) which are stacked in sequence, wherein the material of the surface reconstruction layer (50) is a solid organic acid, and the pKa of the solid organic acid is 3 to 6.
2. The perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The solid organic acid is selected from one or more of the group consisting of monobasic acid, dibasic acid and polybasic acid; Preferably, the pKa of the solid organic acid is 3 to 4; Preferably, the solid organic acid is selected from one or more of the group consisting of lactic acid, malic acid, tartaric acid, citric acid, oxalic acid and succinic acid; Preferably, the thickness of the surface reconstruction layer (50) is 20-40 nm.
3. The perovskite / crystalline silicon tandem solar cell according to claim 1 or 2, characterized in that: A stress release layer (80) is further provided between the first carrier transport layer (20) and the three-dimensional perovskite active layer (30), the material of the stress release layer (80) being an organic polymer, the glass transition temperature of the organic polymer being 90 to 250° C., preferably 100 to 180° C., and the weight average molecular weight being 100 to 15,000,000, preferably 1,000 to 60,000; Preferably, the organic polymer has a structure represented by general formula (I), (II) or (III): Wherein, R1 is selected from hydrogen, C1~C 10 A straight chain or branched chain alkyl group, or a halogen; n1 is selected from any integer between 1 and 60; R2 and R3 are each independently selected from hydrogen, C1-C 10 Straight or branched alkyl, C1~C 10 A straight chain or branched alkoxy group, or a halogen; n2 is selected from any integer in the range of 1 to 30; R4 and R5 are each independently selected from hydrogen, C1-C 10 A straight chain or branched alkyl group, or a halogen; R4 and R5 are the same or different; n3 is selected from any integer in the range of 1 to 20; Preferably, R1 is selected from hydrogen, a C5-C8 straight or branched alkyl group, or F, more preferably hydrogen, and n1 is selected from any integer between 40 and 50; Preferably, the R2 is selected from a C1-C8 straight chain alkoxy group, the R3 is the same as the R2, and the n2 is selected from any integer between 20 and 25; Preferably, the R4 is selected from a branched alkyl group of C1 to C8, the R5 is the same as the R4, and the n3 is selected from any integer of 10 to 15; More preferably, both R2 and R3 are octyloxy; More preferably, both R4 and R5 are 4. The perovskite / crystalline silicon tandem solar cell according to claim 3, characterized in that: The thickness of the stress release layer (80) is 10 to 20 nm; Preferably, the organic polymer is selected from one or more of the group consisting of polystyrene, poly[(m-m-phenylene vinylene)-co-(2,5-dioctyloxy-p-phenylene vinylene)] and poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-B:3,4-B']dithiophene-2,6-diyl]]; Preferably, the three-dimensional perovskite active layer (30) has a thickness of 300 to 500 nm and a band gap of 1.78 to 2.03 eV; Preferably, the two-dimensional perovskite active layer (40) has a thickness of 100 to 300 nm and a band gap of 1.4 to 2.5 eV; Preferably, the material of the three-dimensional perovskite active layer (30) is ABX3, wherein A is selected from CH3NH3 + NH=CHNH3 + and Cs + One or more of the group consisting of; wherein B is selected from Pb 2+ and / or Sn 2+ ; X is selected from Cl - Br - and I - One or more of the groups consisting of; Preferably, the material of the two-dimensional perovskite active layer (40) is L2A m-1 M m X 3m+1 , wherein L is selected from C4H9NH3 + 、C7H 15 NH3 + , C 18 H 37 NH3 + and C 12 H 25 NH3 + One or more of the group consisting of; A is selected from CH3NH3 + 、C2H5NH3 + 、C4H9NH3 + and C7H 15 NH3 + One or more of the group consisting of, M is selected from Pb 2+ and / or Sn 2+ , X is selected from Cl - Br - and I - One or more of the groups consisting of, m is any integer ≥ 2, preferably any integer from 4 to 10.
5. The perovskite / crystalline silicon tandem solar cell according to claim 4, characterized in that: A cathode buffer layer (90) is also included between the second carrier transport layer (60) and the metal electrode layer (70); Preferably, the cathode buffer layer (90) has a thickness of 10 to 30 nm; Preferably, the material of the cathode buffer layer (90) is selected from one or more of the group consisting of 3,3'-(1,3,8,10-tetraanthraquinone [2,1,9-DEF:6,5,10-D'E'F'] diisoquinoline-2,9 (1H,3H,8H,10H)-diyl) bis (N,N-dimethylpropane-1-amine oxide), ethoxylated polyethyleneimine, poly [3-(6-trimethylammoniumhexyl) thiophene] and tin oxide; Preferably, a surface of the metal electrode layer (70) on one side away from the crystalline silicon bottom cell (10) is further provided with an anti-reflection layer (11); Preferably, the anti-reflection layer (11) has a thickness of 50 to 110 nm; Preferably, the material of the anti-reflection layer (11) is one or more selected from the group consisting of magnesium fluoride, calcium fluoride, strontium fluoride, aluminum oxide and aluminum fluoride.
6. The perovskite / crystalline silicon tandem solar cell according to claim 5, characterized in that: The first carrier transport layer (20) is a hole transport layer, and the second carrier transport layer (60) is an electron transport layer; Preferably, the thickness of the first carrier transport layer (20) is 20 to 50 nm; preferably, the thickness of the second carrier transport layer (60) is 10 to 20 nm; Preferably, the thickness of the metal electrode layer (70) is 800-1000 nm; Preferably, the crystalline silicon bottom cell (10) is selected from a TOPCon cell, a HJT cell or an IBC cell; Preferably, the material of the first carrier transport layer (20) is selected from one or more of the group consisting of (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine, poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid, molybdenum oxide, nickel oxide, cuprous oxide and cuprous iodide; Preferably, the material of the second carrier transport layer (60) is selected from titanium oxide, zinc oxide, C 60 One or more of the group consisting of and PCBM; Preferably, the material of the metal electrode layer (70) is selected from one or more of the group consisting of gold, silver and copper.
7. A method for preparing a perovskite / crystalline silicon tandem solar cell according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Step S1, prepare the crystalline silicon bottom cell (10) for standby use; Step S2, preparing a first carrier transport layer (20) on one side surface of the conductive surface of the crystalline silicon bottom cell (10); Step S3, preparing a three-dimensional perovskite active layer (30) on the surface of the first carrier transport layer (20) away from the crystalline silicon bottom cell (10); Step S4, preparing a two-dimensional perovskite active layer (40) on a surface of the three-dimensional perovskite active layer (30) away from the crystalline silicon bottom cell (10); Step S5, coating or spraying a first mixed solution containing a solid organic acid on a surface of the two-dimensional perovskite active layer (40) away from the crystalline silicon bottom cell (10), and obtaining a surface reconstruction layer (50) after a first drying; Step S6, preparing a second carrier transport layer (60) on the surface of the surface reconstruction layer (50) away from the crystalline silicon bottom cell (10); Step S7, preparing a metal electrode layer (70) on the surface of the second carrier transport layer (60) away from the crystalline silicon bottom cell (10), to obtain the perovskite / crystalline silicon stacked solar cell.
8. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 7, characterized in that: The step S5 further comprises mixing the solid organic acid with a first solvent to obtain the first mixed solution; Preferably, in the first mixed solution, the mass concentration of the solid organic acid is 0.5-1 mg / mL; Preferably, the surface reconstruction layer (50) is prepared by spin coating or scraping, and more preferably, the coating amount of the first mixed solution on the surface of the two-dimensional perovskite active layer (40) away from the crystalline silicon bottom cell (10) is 200-1000 mg / cm 2 .
9. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 8, characterized in that: The method further comprises, between step S2 and step S3: mixing an organic polymer with a second solvent to obtain a second mixed liquid, coating or spray-depositing the second mixed liquid on a surface of the first carrier transport layer (20) away from the crystalline silicon bottom cell (10), and obtaining a stress release layer (80) after a second drying; Preferably, in the second mixed solution, the mass concentration of the organic polymer is 1 to 2 mg / mL; Preferably, the stress release layer (80) is prepared by spin coating or scraping, and more preferably, the coating amount of the second mixed liquid on the surface of the first carrier transport layer (20) away from the crystalline silicon bottom cell (10) is 200-1000 mg / cm 2 ; Preferably, the first solvent and the second solvent are each independently an alcohol solvent; more preferably, the alcohol solvent is one or more selected from the group consisting of ethanol, isopropanol, n-butanol and isooctyl alcohol; Preferably, the temperature of the first drying and the second drying are independently 90 to 200° C., and the time is 10 to 20 minutes.
10. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 7, characterized in that: The method further includes between step S6 and step S7: preparing a cathode buffer layer (90) on a surface of the second carrier transport layer (60) away from the crystalline silicon bottom cell (10); preferably, the cathode buffer layer (90) is prepared by magnetron sputtering; Preferably, after step S7, the method further comprises: preparing an anti-reflection layer (11) on a surface of the metal electrode layer (70) on a side away from the crystalline silicon bottom cell (10); more preferably, the anti-reflection layer (11) is prepared by a vapor deposition method; Preferably, in step S3, the three-dimensional perovskite active layer (30) is prepared by spin coating, blade coating or spray deposition, and is subjected to a first annealing treatment; Preferably, in the step S4, the two-dimensional perovskite active layer (40) is prepared by spin coating, blade coating or spray deposition, and is subjected to a second annealing treatment; Preferably, the temperature of the first annealing treatment is 100-160°C and the time is 10-25 minutes; Preferably, the second annealing treatment is performed at a temperature of 100 to 130° C. and for a time of 10 to 20 minutes.